Unsolved [compact disc, unabridged] - Patterson, James, 1947-; Ellis, David, 1967- (Hachette Audio, 2019)
When a series of suspicious fatal accidents baffle FBI agent Dockery, she finds her investigation complicated by her ex and a killer who is somehow one step ahead.